USING THE PROJECT METHOD IN THE DEVELOPMENT OF STUDENTS' FOREIGN LANGUAGE COMMUNICATIVE COMPETENCE IN THE FIELD OF INFORMATION TECHNOLOGIES (TAMADDUN NURI JURNALI, 2025)
This article explores the role of interactive teaching methods, particularly the project-based method, in developing foreign language communicative competence among students majoring in information technology. The effectiveness of this method is demonstrated through a student-led independent project to create a university newspaper. The article highlights how project-based learning contributes to the development of speaking skills, communication abilities, and teamwork competence.